Proteomic profiling of cerebrospinal fluid uncovers distinctive pathophysiological changes and potential biomarkers in pediatric tubercular meningitis - Wei, Jing; Zhu, Liang; Jian, Binglin; Yu, Yuncui; Hu, Bing; Guo, Lingyun; Hu, Huili; Dou, Zhenzhen; Liu, Linlin; Liu, Gang; Guo, Peng (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionTubercular meningitis (TBM) is a serious pediatric infection with high mortality rates. This research aimed to characterize the alterations in cerebrospinal fluid (CSF) proteome in TBM and to identify biomarker panels that can distinguish it from other central nervous system infections. MethodsWe retrospectively analyzed the CSF proteome from 104 patients, including 7 TBM, 28 with purulent meningitis (PM), 20 with viral meningitis (VM), 9 with cryptococcus neoformans meningitis (CNM), 30 non-CNS infected controls (Ctrl), and 10 brain disease (BD) controls. ResultsThe TBM proteome displayed greater similarity to that of PM patients. A total of 120 cytokines and receptors were significantly dysregulated in TBM CSF. Pathway analysis indicated marked upregulation of complement activation, fibrin clot formation, and microautophagy signaling, along with significant suppression of collagen degradation in TBM. Biomarker panels were established, including F2 and TYMP to differentiate TBM from PM (AUC=0.874, 95% CI, 0.748-0.999), ENPP2 and WARS1 to differentiate TBM from VM (AUC=0.929, 95% CI, 0.929-1), F12, APOM and CD163 to differentiate TBM from CCM (AUC=0.993, 95% CI, 0.869-1), and HLA-B and MGAT1 to differentiate TBM from Ctrls (AUC=0.934, 95% CI, 0.825-1).DiscussionThis research will provide a highly valuable proteomics resource for a better understanding of TBM pathogenesis, yielding insights into important differential diagnostic biomarkers and potential therapeutic targets in pediatric TBM.